The law of treaties in Africa: Exploring the Southern African development community mutual defence pact - Lucid Chirozva; Raymond Damba (Annals of Justice and Humanity, 2021)
Purpose: The article explores the structural and fundamental discussions connected with the law of treaties with a detailed orientation towards the Southern African Development Community Mutual Defence Pact (SADC MDP) of 2003 and the Vienna Convention on the Law of Treaties of 1969. The study was informed by the principle of pacta sunt servanda. Research Methodology: The study employed a desktop research approach and a systematic review of a number of secondary sources on the law of treaties. Results: It was established that the SADC MDP drafters were cognizant of the principles of international law the treaties in framing this sub-regional legal instrument. Some articles within the SADC MDP are ignorant of the political realities of the international system. Limitations: The realism school of thought was used as the tool of analysis for this study in order to unravel the SADC MDP from a political perspective. Contributions: This study sought to educate jurists, policymakers, and implementers of laws and policies in the 21st century.